2018
DOI: 10.1532/hsf.1851
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Rho Kinase and Its Mechanism in the Left Atrial Appendage in Patients with Atrial Fibrillation

Abstract: To study the expression of Rho kinase (Rho associated coil forming protein kinase-1, ROCK-1) and its substrate myosin phosphatase target subunit 1 (myosin phosphatase target subunit-1, MYPT-1), connexin 40 (Cx40) and connexin 43 (Cx43) in the left atrial appendage of patients with atrial fibrillation, and explore the role of ROCK signaling pathway in patients with atrial fibrillation and its underlying mechanism. Methods: 40 patients undergoing open heart surgery were divided into two groups; atrial fibrillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Recently, the involvement of the ROCK pathway was documented using left atrial appendage biopsies of AF patients vs. those with sinus rhythm which showed increased expression of ROCK and MYPT-1 that correlated with the expression of Cx40, an integral membrane protein of heart gap junctions, fundamental for the rapid cell-cell transfer of action potential [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the involvement of the ROCK pathway was documented using left atrial appendage biopsies of AF patients vs. those with sinus rhythm which showed increased expression of ROCK and MYPT-1 that correlated with the expression of Cx40, an integral membrane protein of heart gap junctions, fundamental for the rapid cell-cell transfer of action potential [10].…”
Section: Discussionmentioning
confidence: 99%
“…This last finding then raised questions as to the exact role(s) of the RhoA/ROCK pathway of Ang II transduction in the molecular mechanisms linked to AF. Just recently, Chen et al [10] using human left atrial appendages from patients undergoing cardiac surgery found an overexpression of ROCK, its metabolic downstream mediator myosin phosphatase target subunit-1 (MYPT-1), known as the marker of ROCK activity, as well as Cx40 in those patients with documented AF.…”
Section: Introductionmentioning
confidence: 99%
“…Some athletes may develop an extreme cardiac remodelling process, including atrial structure and function changes [12][13], worse ventricular performance post-effort [6], and appearance of arrhythmias in the long-term follow-up [24]. Regarding the physiopathology of the previous process, the ROCK signaling pathway could play an important role in electrical properties changes in atrial tissue (connexin expression), as Chen et al (2018) showed studying the LA appendage in patients with and without atrial fibrillation [25]. In our study, the HT group showed higher: left cardiac cavities remodelling, ROCK activity and sports performance than other groups; probably these pathways related to cell survival to stress and cardiac remodelling allow to athletes a better adaptation and performance to extreme efforts, but there could be an individual point for each subject in which a poor adaptation may be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Among the implications of increased left ventricular mass, atrial fibrillation is the most frequent arrhythmia in patients with kidney failure with or without renal replacement therapy and is associated to marked MYPT-1 phosphorylation [68]. Cardiac remodeling, including atrial myocytes structural and electrical alterations, greatly contributes to the pathogenesis of atrial fibrillation.…”
Section: Oxidative Stress and Dialysis Proceduresmentioning
confidence: 99%